A resolução de problemas no contexto do estágio curricular supervisionado: dificuldades e limites de licenciandos em matemática - Proença, Marcelo Carlos de; Pirola, Nelson Antonio [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2014)
The aim was to investigate the difficulties and limits of four future mathematics teachers to conduct classes in regencies approach of problem solving. Based on participation in a course this approach, undergraduates elaborated three didactic sequences, which were taught by the activity of conducting classroom discipline Supervised Curricular Training. After this work, participated in an individual interview to report what had developed in classroom. The results showed difficulties in the following aspects: in the elaboration of didactic sequences; in providing an environment for discussion of resolution strategies students. Furthermore, the data analysis showed limits related: the lack of space at the school teacher to allow implementation of lessons developed; lack of basic mathematical knowledge of the students.

O objetivo foi o de investigar as dificuldades e os limites de quatro futuros professores de Matemática para realizar regências de aulas na abordagem da resolução de problemas. Com base na participação em um curso nessa abordagem, os licenciandos elaboraram três sequências didáticas, as quais foram ministradas por meio da atividade de regência de aula da disciplina de Estágio Curricular Supervisionado. Após esse trabalho, participaram de uma entrevista individual para relatar o que tinham desenvolvido nas aulas. Os resultados mostraram dificuldades nos seguintes aspectos: na elaboração das sequências didáticas; em propiciar um ambiente de discussão das estratégias de resolução dos alunos. Além disso, a análise dos dados mostrou limites relacionados: à falta de espaço pelo professor da escola para permitir a realização das aulas elaboradas; à falta de conhecimentos matemáticos básicos dos alunos da escola.
Problem solving in the context of curricular supervised training: difficulties and limits of undergraduates in mathematics
Keywords: Degree in mathematics; Problem solving; Initial teacher education; Supervised curricular training; Teaching of mathematics; Licenciatura em matemática; Ensino de matemática; Resolução de problemas; Formação inicial; Estágio curricular supervisionado